FORMULASI SEDIAAN GEL ANTISEPTIK DAUN SIRIH HIJAU (Piper betle linn) DENGAN BASIS BIJI RAMI (Linum usitatissimum) DAN PENAMBAHAN SARI JERUK NIPIS (Citrus x aurantiifolia) SEBAGAI AROMA - Bilqies, Zalzabila Lusyana Fauziah; Andriani, Susi; Yanto, Elih Sutisna (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: Green betel has an excess of antiseptic power which is more dominant than other betel, because its strong antiseptic power is often used empirically to treat various diseases. The growing public desire to use natural ingredients or “back to nature” has been responded by many topical products with active plant ingredients for health care, cosmetics and disease prevention. Piper batle Linn or green betel is one of the plants known to have antiseptic properties. The traditional use of green betel is usually by boiling betel leaves then boiled water is used to rinse and clean other parts of the body, or crushed betel leaf and then attached to the wound (Lindawaty, 2009). Objective: This study aims to make an antiseptic gel formulation based on flaxseed and added with lime juice as an aromatic, to make a stable and homogeneous antiseptic gel and to determine the pH that was tested at room temperature and has a good shape, color and smell. Method: This study uses action research design. This action research design aims to identify and find solutions to a problem under study. In this study, using 4 cycles between important components, such as planning, action, observation, and reflection. This research planning is in the form of work planning stages that must be carried out at the time of the research, then followed by research and observation of the results of the research then analyzed as a reflection of the researcher's achievements at the time of the research. Results: The result of drying shrinkage from the simplicia used was betel leaf of 73.4% based on the pH stability test, which increased the preparation, homogeneous and lasted for 20 days. Conclusion: the conclusion of this research is Formula II and III can last for 20 days at room temperature storage (15-30oC) with an initial pH of 4 and a final pH of 6, brownish yellow, distinctive smell of lime and betel, slippery texture. At cold temperatures (± 4oC), formulas II and III can last for 21 days.